PENGARUH CITRA INSTITUSI TERHADAP PERSEPSI KUALITAS DAN PERSEPSI NILAI SERTA DAMPAKNYA PADA KEPERCAYAAN MAHASISWA : (Survey di STIE Cipasung Tasikmalaya) - Raisa Hillia Aini Syifa (JURNAL EKONOMI PERJUANGAN, 2021)
The purpose of this study is to analyze the effect of institutional image on perceived quality and perceived value which have an impact on consumer trust. The research method used was a survey method using a questionnaire as a primary data collection tool that was distributed to 181 respondents who were active students at STIE Cipasung Tasikmalaya. The analytical tool used in this study is SEM, and shows that institutional image has a significant influence on perceived quality and perceived value but is not proven to have a direct effect on student trust. Quality perception has a significant effect on student trust, but the perceived value cannot be proven to influence student trust. Perceived quality can also mediate the interaction of an institution’s image with trust. Therefore, the students trust of STIE Cipasung Tasikmalaya can be shaped by their perceived quality based on the image of the institution they have.